(untitled) (Bioscience Journal, 2022)
Intercropped systems with Conilon coffee might provide a better environment for coffee production. The aim of this study was to assess the microclimate and development of Conilon coffee intercropped with papaya trees. Papaya was planted with spacing of 3.20 x 2.40 m. The coffee trees were planted after eight months, with spacing of 3.20 x 1.60 m, in-between papaya trees (in the same row). The measurements were taken 0, 40 and 80 cm away from the coffee plants, both in the north and south direction. Concomitantly, an adjoining full sunlight coffee system (not intercropped) was also assessed. The measurements included atmospheric parameters (temperature, irradiance, and relative humidity) and vegetative parameters for the coffee plants (leaf area, relative chlorophyll index, length of plagiotropic branches, length of orthotopic branches and number of nodes) in three periods of the year. The intercropped system of Conilon coffee and papaya trees led to a decrease in both irradiance and temperature, and higher means of relative humidity during daytime in all the periods assessed, which contributes to a better environment for coffee cultivation. The shadow provided by papaya trees in the coffee plants contributed to a higher leaf area but did not affect neither the growth of both plagiotropic and orthotopic branches, nor the number of nodes and the etiolation. The intercropped system of Conilon coffee and papaya trees may be potentially used as a farming system to mitigate climate change.